Government-Sponsored Health Insurance in India : Are You Covered? - La Forgia, Gerard; Nagpal, Somil (2012)
Since independence, India has struggled to provide its people with universal health coverage. Whether defined in terms of financial protection or access to and effective use of health care, the majority of Indians remain irregularly and incompletely covered. Finally, and most recently, a new generation of Government-Sponsored Health Insurance Schemes (GSHISs) has emerged to provide the poor with financial coverage. Briefly, the main objective of these new GSHISs was to offer financial protection against catastrophic health shocks, defined in terms of an inpatient stay. Between 2007 and 2010, six major schemes have emerged, including one sponsored by the Government of India (GOI) and five state-sponsored schemes. This new wave of schemes provides fully subsidized coverage for a limited package of secondary or tertiary inpatient care, targeting below poverty populations. Similar to the private voluntary insurance products in the country, ambulatory services including drugs are not covered except as part of an episode of illness requiring an inpatient stay. The schemes have organized hospital networks consisting of public and private facilities, and most care funded by these schemes is provided in private hospitals. Ostensibly, the objective of any health insurance scheme is to increase access, utilization, and financial protection, and ultimately improve health status. Due to lack of evaluations and analyses of household data, the authors of this book do not examine the impact of health insurance in terms of these objectives. This book is not meant to highlight problems of the GSHISs, but rather to raise potential challenges and emerging issues that should be addressed to ensure the long-term viability of these schemes and secure their place within the health finance and delivery system.